A Review: Cavitation on Dam Spillway - Zanial W.N.C.W.; Zawawi M.H.; Sidek L.M.; Abas M.A.; Dullah H.; Hassan N.H.; Radzi M.R.M.; Rahman A.H.A. (Springer Science and Business Media Deutschland GmbH, 2024)
The spillway is a component of the dam's flow control channel that serves to enhance regulation and boost the flow rate that passes through the spillway building. By rapidly changing local pressure and velocity, surface cracks can cause cavitation damage. Cavitation is defined as the phenomenon where pressure is less than 1atm, resulting in air bubbles on the building surface, causing holes due to the release of aggregate grains on the construction surface. Unremoved cavitation can endanger the bottom surface of the spillway due to scouring/erosion. Damage to the canal floor due to continuous scouring can cause water to enter through the scour cracks, thus disrupting the stability of the spillway. Hence, this article mainly discusses a cavitation study that was conducted at the dam spillway. Based on the review in this paper, to determine hydraulic cavitation features of a spillway, most research employ prototype observation, physical model observation, and numerical model simulation. Furthermore, more comprehensive results produced by numerical simulations than by actual investigation is proved by previous research reviewed in this paper. However, using both a physical model and a numerical simulation to determine a spillway's hydraulic cavitation characteristics is reliable. The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd. 2023.